2002
DOI: 10.1055/s-2002-35071
|View full text |Cite
|
Sign up to set email alerts
|

Qualified Rescue by Ski Patrols - Safety for the Skier

Abstract: This study aims to determine whether the training of ski-patrol teams is still adequate in view of a marked change in injury patterns. All accidents which occurred during two winter seasons (n = 579, 583 patients) in the Oberwallis ski area in Switzerland are analysed retrospectively. As the analysis of the accidents' data are similar to other studies and first aid training is standardised throughout Switzerland, the results of this study can be viewed as representative for other areas of Switzerland. The gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
14
1
Order By: Relevance
“…Küpper et al 13 found that 89.5% of Swiss ski patrol injury diagnoses were at least "mostly correct." The accuracy of ski patrollers' injury assessments is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Küpper et al 13 found that 89.5% of Swiss ski patrol injury diagnoses were at least "mostly correct." The accuracy of ski patrollers' injury assessments is not well established.…”
Section: Introductionmentioning
confidence: 99%
“…9 Similarly, a recent study that examined the accuracy of injuries reported by ski patrols compared with doctors' diagnoses confirmed that the data from ski patrols were correct or mainly correct in 89.5% of all cases. 10 To our knowledge, no assessment has been made of the reliability of information on risk factors recorded by ski patrols. Therefore, the purpose of this study was to document the consistency of reporting of information on risk factors between a standard accident report form used by ski patrols and a follow up mail questionnaire or telephone interview.…”
mentioning
confidence: 99%
“…In this context, Küpper et al emphasized the significance of on-scene suspicion of multiple injuries, which was the most frequent underdiagnosed injury category in a study sample considered representative for Swiss ski regions [19]. Almost all current prehospital and early in-hospital care algorithms contain triage-like primary assessments.…”
Section: Discussionmentioning
confidence: 99%
“…In general, standardized algorithms in prehospital and in-hospital care of the injured are discussed controversial [13-21]. Absence of dedicated standardized algorithms was previously associated with inadequate transfer patterns, increased morbidity, and transfer costs [19-21]. Nevertheless and to the best knowledge of the authors, dedicated on-slope triage protocols do not exist and evidence for the effectiveness and efficiency of comparable algorithms is missing.…”
Section: Introductionmentioning
confidence: 99%